Efektivitas Konseling Terhadap Pemilihan Metode Kontrasepsi Efektif - Dewi Rakhmawati; Khoirul Anam (Universitas Islam Jember, 2022)
Family Planning contraception is one of the efforts to achieve prosperity by providing marital advice , treatmenti, infertility and birththinning. The low selection of Intra Uterine Device contraceptives atfertile copule at the Mumbulsari Health Center, Jember Regency in 2022, the cause is that there is still a lack of counselling oncontraceptive methods as a whole. This study aims to determine theeffectiveness of counselling in selecting effective contraceptivemethods at fertile couple at the Mumbulsari Health Center, Jember Regency, in 2022. The type of research is analytical with a pre-posttest design. The sample was a fertile age couple of 92 people , asampling technique with a simple random sampling technique . Thefree variable in this study is counselling,while the dependent variableis the selection of contraceptive methods. The analysis used isChii-isquarei.It was obtained that the p - value was 0.000 with an αof 0.05. Because the p-Value < α, H0 was rejected and H1 wasaccepted, which means that it was proven that the effectiveness ofcounselling on the selection of effective contraceptive methods at thefertile age couple at the Mumbulsari Health Center, Jember Regencyin 2022. Health workers are expected to study more deeply thequality of services that have been provided and improve obstetricservicesi.